Translation regulatory long non-coding RNA 1 (TRERNA1) sponges microRNA-23a to suppress granulosa cell apoptosis in premature ovarian failure. Issue 2 (1st February 2022) - Zhang, Lili; Mao, Bin; Zhao, Xiaodong; Yuan, Yue; Wang, Wei; Lin, Shaohua
ABSTRACT: Translation regulatory long non-coding RNA 1 (TRERNA1) plays critical roles in cancer biology. We predicted the direct interaction of TRERNA1 with microRNA (miR)-23a, which promotes granulosa apoptosis. Granulosa apoptosis is involved in premature ovarian failure (POF). This study was therefore carried out to explore the involvement of TRERNA1 and miR-23a in POF. The expression of TRERNA1 and miR-23a in POF and control groups were detected by RT-qPCRs. The subcellular locations of TRERNA1 in granulosa cell line COV434 was detected by subcellular fractionation assay. The interaction between TRERNA1 and miR-23a was predicted using IntaRNA2.0. The direct interaction between COV434 and miR-23a was explored with RNA pull-down assay. In granulosa cells, the direct interaction between TRERNA1 and miR-23a was verified by overexpression assay. Cell apoptosis assay was performed to evaluate cell apoptosis. Both TRERNA1 and miR-23a were downregulated in POF. In addition, TRERNA1 was detected in both cytoplasm and nuclear samples of granulosa cells, and directly interacted with miR-23a. TRERNA1 did not affect the expression of miR-23a in granulosa cells, while TRERNA1 suppressed the role of miR-23a in enhancing cell apoptosis. In conclusion, TRERNA1 may sponge miR-23a to suppress granulosa cell apoptosis in POF.